High-pressure effect on the superconductivity of NaAlGe and pressure-induced structural phase transition - E. Karaca; D. Errandonea (Results in Physics, 2023)
The structural, electronic, phonon, and electron–phonon properties of NaAlGe have been investigated under high pressure by means of density-functional theory simulations. The calculated electronic structure and density of states reveal that the electronic states near the Fermi level, which are responsible for electrical conductivity, are mostly composed of Ge 4p states. The largest contribution to the average electron–phonon coupling parameter is from Ge-related vibrations, and this parameter is calculated to be λ∼ 0.609. The superconducting critical temperature at ambient pressure is calculated to be Tc = 2.31 K. This temperature agrees with the previously experimentally obtained value of 1.80 K. The electronic density of states at the Fermi energy, λ, and Tc decrease as pressure is increased, and superconductivity is suppressed at 12 GPa. We also report the phonon dispersion at different pressures showing that NaAlGe develops a dynamical instability at 13 GPa favoring a structural phase transition Based on enthalpy calculations the crystal structure of the high-pressure phase has been proposed to be orthorhombic and described by space group Pnma. This phase does not exhibit superconductivity. The pressure dependence of unit-cell parameters and Raman- and infrared-active phonons of the low-pressure and high-pressure phase is also reported.